From roles to standards: a dynamic maintenance approach using incentives - Ramón Hermoso (2015)
Social coordination has been addressed in multi-agent systems, making use of concepts such as institutions, norms, commitments, conventions, roles, or trust. In this paper, we argue the need to tackle open and dynamic environments with yet another concept: the notion of a standard, seen as a measurable and non-committing expectation. Not much work has been done in the field of multi-agent systems addressing the evolving nature of roles, especially in open systems, in which changes in the population bring about changes in the expectations generated from roles. Using standards measured from roles as the focus of attention, we propose an incentive-based mechanism to maintain roles over time. This approach is put in contrast with reorganization, which is needed when incentives are not cost-effective. Different search algorithms are proposed to illustrate incentive-based maintenance. Some empirical results are shown based on the principal-agent model from economics.